Comparing the Clinical Utility of the Infant Developmental Inventory With the Ages and Stages Questionnaire at 9-Month Well-Child Visits - Lindsay R. Hunter; Mioki R. Myszkowski; Shirley K. Johnson; Paulette V. Rostad; Amy L. Weaver; Brian A. Lynch (SAGE Publishing, 2015)
Objective: The purpose of our study was to compare the clinical utility of administering 2 recommended developmental screening instruments, the Infant Developmental Inventory (IDI) and the Ages and Stages Questionnaire (ASQ), at 9-month well-child visits in paper format. Methods: Outcomes of the 2 screens, including correct completion and interpretation by clinician, time of visit, and screen outcome were compared. Results: Out of 33 children administered the ASQ and with documented scores, 12 (36.4%) did not receive passing scores, while 5 (12.2%) of the 41 children administered the IDI did not receive passing scores ( P = .014). Out of 41 IDI screens, 12 (29.3%) were completed incorrectly, while there were no ASQ screens completed incorrectly ( P < .001) by caregivers. Conclusion: In our pilot study, the ASQ is more often completed correctly by caregivers and identifies more children at risk for delay as compared with the IDI. Additional larger scale studies are needed to evaluate the usefulness of developmental screening tools when used within primary care practice.